Language deterioration in bilingual Alzheimer's disease patients: A longitudinal study. (August 2017) - Calabria, Marco; Cattaneo, Gabriele; Marne, Paula; Hernández, Mireia; Juncadella, Montserrat; Gascón-Bayarri, Jordi; Sala, Isabel; Lleó, Alberto; Ortiz-Gil, Jordi; Ugas, Lidia; Blesa, Rafael; Reñé, Ramón; et al.
Abstract: In the context of bilingual research, little is known about the effects of neurodegenerative disorders (NDs) on the processing of two languages in a bilingual. In a recent cross-sectional study, we showed that Mild Cognitive Impairment (MCI) and Alzheimer's disease (AD) had similar effects on lexico-semantic processes in the two languages of highly proficient bilinguals (Costa et al., Neuropsychologia, 2012, 50, 740–53). In the present longitudinal study, we extend this finding by looking at the pattern of language deterioration over time in the same population of Catalan-Spanish bilingual patients. All the participants completed three language-processing tasks (picture naming, word translation and word comprehension), both in their dominant (L1) and non-dominant (L2) language. At one year, the final group was made up of 50 patients: 15 with MCI and 35 with AD. For AD but not MCI, the language deterioration over time was the same in both languages, as previously reported in the cross-sectional study. The results are discussed in the frame of the hypothesis of shared lexico-semantic processing in highly proficient bilinguals and the influence of executive control deficits in language production. Highlights: Language performance of bilingual AD and MCI patients are compared longitudinally. AD had similar effects on the two languages in production tasks. Proficient bilinguals have shared lexico-semantic processing for the two languages.